2011
DOI: 10.1093/ndt/gfr070
|View full text |Cite
|
Sign up to set email alerts
|

Remote indigenous peritoneal dialysis patients have higher risk of peritonitis, technique failure, all-cause and peritonitis-related mortality

Abstract: This registry analysis demonstrates that non-metropolitan PD patients, especially remote indigenous patients, have higher complication rates, suggesting that environmental factors are important in determining PD outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 9 publications
7
58
0
Order By: Relevance
“…Our findings suggest that a racial ethnic disparity may exist for survival on peritoneal dialysis for Aboriginals in Canada. Previous literature has shown conflicting results on peritoneal dialysis and mortality in Aboriginals (10,12,14,15,17). Our findings are consistent with a recent report from Manitoba, where we investigated 161 Aboriginal patients compared with 566 non-Aboriginal patients on peritoneal dialysis and found an increase in mortality (adjusted HR=1.48, 95% CI=1.07-2.03) and peritonitis (adjusted HR=1.79, 95% CI=1.35-2.36) among Aboriginals (10,17).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings suggest that a racial ethnic disparity may exist for survival on peritoneal dialysis for Aboriginals in Canada. Previous literature has shown conflicting results on peritoneal dialysis and mortality in Aboriginals (10,12,14,15,17). Our findings are consistent with a recent report from Manitoba, where we investigated 161 Aboriginal patients compared with 566 non-Aboriginal patients on peritoneal dialysis and found an increase in mortality (adjusted HR=1.48, 95% CI=1.07-2.03) and peritonitis (adjusted HR=1.79, 95% CI=1.35-2.36) among Aboriginals (10,17).…”
Section: Discussionsupporting
confidence: 89%
“…This finding is congruent with studies from Alaska and the United States that also demonstrated similar outcomes for Indigenous peoples on intermittent hemodialysis compared with Caucasians (6,13). However, this finding is in direct contrast to some findings from Australia and New Zealand, where Aboriginals on peritoneal dialysis have worse outcomes with an increased risk of peritonitis, technique failure, hospitalizations, and mortality (14)(15)(16). Recently, we have also reported an increase in peritonitis and mortality rates in Aboriginals relative to Caucasians undergoing peritoneal dialysis in Manitoba, Canada (10,17).…”
Section: Introductionsupporting
confidence: 82%
“…In line with our findings, Tonelli et al (14) reported that Canadian patients living Ͼ300 km from a dialysis center had a significantly lower risk of technique failure compared with those living closer (50 km). In contrast, Lim et al (15) recently reported in a large Australian PD population that patients residing in a nonmetropolitan location, especially remote indigenous, have a greater peritonitis risk. Further studies will need to be designed to particularly address this issue.…”
Section: Discussionmentioning
confidence: 84%
“…In a previous study, patients living far from the nearest dialysis center presented significantly higher chance of being prescribed PD (13), and therefore the distance from the center could potentially influence PD outcome and peritonitis rate (14,15); however, this hypothesis has not been evaluated in detail. Socioeconomic condition has also been described as a factor determining peritonitis risk (16), although isolated analysis of the effect of income has not been studied in depth.…”
Section: Introductionmentioning
confidence: 97%
“…Peritonitis is associated with an increased risk of technique failure and mortality among peritoneal dialysis (PD) patients (1)(2)(3). Along with improved connectology and training methods, antibiotic prophylaxis given before high-risk procedures has probably contributed to an overall decline in peritonitis rates since the early 1990s.…”
Section: Gastroscopy-related Peritonitis In Peritoneal Dialysis Patientsmentioning
confidence: 99%